2011
DOI: 10.1103/physrevlett.107.178103
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian Fluctuations Resulting from Power-Law Trapping in a Lipid Bilayer

Abstract: Anomalous diffusion in lipid bilayers is usually attributed to viscoelastic behavior. We compute the scaling exponent of relative fluctuations of the time-averaged mean square displacement in a lipid bilayer, by using a molecular dynamics simulation. According to the continuous time random walk theory, this exponent indicates non-Gaussian behavior caused by a power-law trapping time. Our results provide the first evidence that a lipid bilayer has not only viscoelastic properties but also trapping times distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
116
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(125 citation statements)
references
References 31 publications
(54 reference statements)
9
116
0
Order By: Relevance
“…Thus, the RSD,σ EB (t), is not helpful to characterize the ergodicity breaking in this case. Using the relative fluctuation defined by [8,42] instead of the RSD, we can clearly see the ergodicity breaking in the case of …”
Section: Ordinary Renewal Processmentioning
confidence: 97%
“…Thus, the RSD,σ EB (t), is not helpful to characterize the ergodicity breaking in this case. Using the relative fluctuation defined by [8,42] instead of the RSD, we can clearly see the ergodicity breaking in the case of …”
Section: Ordinary Renewal Processmentioning
confidence: 97%
“…The RF and RSD behave in a similar way, and it is reported that these quantities can characterize some dynamical properties of the system [15][16][17].…”
Section: Introductionmentioning
confidence: 93%
“…Thus it is important to calculate the statistical quantities such as the average and standard deviation of the TAMSD. The magnitude of the fluctuation of the TAMSD can be quantitatively characterized by the relative fluctuation (RF) [15,16] or the relative standard deviation (RSD) [12,14,17]: R(t; ∆) ≡ |δ 2 (∆; t) − δ 2 (∆; t) | δ 2 (∆; t) ,…”
Section: Introductionmentioning
confidence: 99%
“…A clear non-Markovian effect was also observed in the time correlation function of the random force. Note that the non-Gaussian fluctuation is a general feature in non-equilibrium systems ranging from the cosmoscopic [40,41], mesoscopic [42,43], to microscopic systems [44]. Furthermore, as discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%